Liquid-liquid phase separation in super enhancer-driven oncogenesis: mechanisms, immune evasion, and therapeutic implications - Yu, Ruoxi; Sun, Deyu; Zhang, Chuang (Frontiers in Cell and Developmental Biology, 2025)
Liquid-Liquid Phase Separation (LLPS) allows biomolecules to form membrane-less organelles or condensates through weak multivalent interactions. Recent studies have revealed the critical role of LLPS in super-enhancer (SE)-associated tumorigenesis, progression, and immune evasion. This mini-review summarizes recent advances in the role of LLPS in SE-driven oncogenic and immune evasion processes, while discussing its potential therapeutic implications in cancer. Current evidence indicates that LLPS regulates the expression of tumor-associated genes through multiple mechanisms, such as facilitating transcription factor recruitment, promoting chromatin looping, modulating chromatin topology, and maintaining chromatin accessibility. Notably, LLPS-associated SEs functionally regulate not only tumor cells but also immune cells within the tumor microenvironment, contributing to tumor immune evasion. Thus, understanding the relationship between LLPS and SEs is crucial for elucidating the mechanisms underlying tumor initiation and progression. These insights may provide foundational evidence for developing novel anti-tumor therapeutic agents.